Soziale Arbeit im Kontext Schule Aktuelle Entwicklungen in Praxis und Forschung in der Schweiz - Chiapparini, Emanuela (Verlag Barbara Budrich, 2018)
The anthology provides insight into fields of action and offers of social work in the school context and focuses for the first time on various current developments in German- and French-speaking Switzerland. In addition, the opportunities and challenges of social work in schools are presented and discussed with practical and research-based contributions.